Profits: A Case Of Exchange Rate Volatility - Gatut L Budiono; Agnesya Firdayasa (Jurnal Akuntansi, 2017)
The  purpose  of  this  research  was  to  measure  theeffect  of  exchange  ratevolatility  on  the  companies’  profit  in  food  and  beverages  sub  sector  with  revenue  andexpenses as an intervening. The analysis technique used in this research was regressionand path analysis.  The financial statement and middle exchange rate of first quarter of 2012 to2015 third quarter IDX and BIsecondary data was incorporated in the research.These  research  result  showed  that  the  exchange  rate  volatility  may  affect  companies’profit in food and beverages sub sector either directly or indirectly.